Influence of dry herbal extracts on pentylenetetrazole-induced seizures in mice: screening results and relationship “chemical composition – pharmacological effect” - Tsyvunin, Vadim; Shtrygol’, Sergey; Prokopenko, Yuliya; Georgiyants, Victoriya; Blyznyuk, Nataliya (ScienceRise: Pharmaceutical Science, 2016)
Aim. Screening of 48 dry extracts of plants belonging to 18 species of 8 families not studied before on anticonvulsant activity, to analyze the chemical composition for the extracts with proved anti- and proconvulsant activity, and to estimate the connection of the effect of herbal products and their phytochemical composition. Methods. On the model of pentylenetetrazole-induced seizures in mice the influence of 48 dry herbal extracts with varied chemical composition has been investigated. Extracts were standardized by the content of alkaloids, flavonoids and polyphenols according to European Pharmacopoeia methods (HPTLC, HPLC, UPLC, GC-MS). Results. By the integral indicator of efficacy – reduction of the mortality rate – it has been found that 11 of herbal preparations have significant anticonvulsant properties, 10 extracts act as proconvulsants, and the remaining 27 extracts have practically no effect on experimental convulsions. It has been established that there is a relationship between the pharmacological effect of preparations and phytochemical composition of the plant being extracted as well as the host species (for parasitic species – Viscum album) and the degree of polarity of the extracting agents. For the extracts with expressed anti- and proconvulsant features the chemical composition has been investigated. Conclusion. The detailed analysis of relationship between phytochemical composition and influence of the extracts on the experimental seizures has found that anticonvulsant peculiarities of extracts most probably depend on rutin high content, but for the herbal medicines with proved proconvulsant properties the role of individual biologically active compounds has not been defined